Gendered Language Practices in Digital Poetry Discourse - Laila Ulsi Qodriani; Aulia Tri Rahayu; M. Yuseano Kardiansyah (Leksema: Jurnal Bahasa dan Sastra, 2026)
This study investigates the linguistic representations of gender in viral online poetry published on three major social media platforms—Instagram, Twitter/X, and TikTok—in Indonesia between January 2023 and December 2024. Employing a qualitative multimodal approach that integrates gender-based linguistic analysis, digital semiotics, and Critical Discourse Analysis (CDA), the study examined 319 viral poems authored by writers of different gender identities. The findings reveal significant and consistent differences in the language patterns of female and male poets. Female writers predominantly employed emotional diction (87%), nature and body metaphors (78% and 65% respectively), and explicit expressions of vulnerability (68%), while male writers favored abstract and conceptual diction (68%), spatial and war metaphors (72% and 58%), and social critique. Digital symbols such as emojis, typography, and hashtags further reinforced these gendered linguistic identities. Notably, an emergent queer poetic voice was identified (12%), challenging binary gender norms through deconstructive metaphors and transgressive digital symbols. The study contributes to the theorization of digital sociolinguistics and the gendered nature of computer-mediated communication (CMC) in the Indonesian digital literary landscape.